Efficacy and safety of anticoagulants for postoperative thrombophylaxis in total hip and knee arthroplasty: A PRISMA-compliant Bayesian network meta-analysis. - Tailai He; Fei Han; Jiahao Wang; Yihe Hu; Jianxi Zhu (PLoS ONE)
Objective To search, review, and analyze the efficacy and safety of various anticoagulants from randomized clinical trials (RCTs) of anticoagulants for THA and TKA. Design PRISMA-compliant Bayesian Network Meta-analysis. Data sources and study selection The databases of The Medline, Embase, ClinicalTrial, and Cochrane Library databases were searched until March 2017 for RCTs of patients undergoing a THA or TKA. Main outcomes and measures The primary efficacy measurement was the venous thromboembolism Odds ratio (OR). The safety measurement was the odds ratio of major or clinically relevant bleeding. OR with 95% credibility intervals (95%CrIs) were calculated. Findings were interpreted as associations when the 95%CrIs excluded the null value. Results Thirty-five RCTs (53787 patients; mean age range, mostly 55-70 years; mean weight range, mostly 55-90 kg; and a higher mean proportion of women than men, around 60%) included the following Anticoagulants categories: fondaparinux, edoxaban, rivaroxaban, apixaban, dabigatran, low-molecular-weight heparin, ximelagatran, aspirin, warfarin. Anticoagulants were ranked for effectiveness as follows: fondaparinux (88.89% ± 10.90%), edoxaban (85.87% ± 13.34%), rivaroxaban (86.08% ± 10.23%), apixaban (68.26% ± 10.82%), dabigatran (41.63% ± 12.26%), low-molecular-weight heparin (41.03% ± 9.60%), ximelagatran (37.81% ± 15.87%), aspirin (35.62% ± 20.60%), warfarin (9.89% ± 9.07%), and placebo (4.56% ± 6.37%). Ranking based on clinically relevant bleeding events was as follows: fondaparinux (14.53% ± 15.25%), ximelagatran (18.93% ± 17.49%), rivaroxaban (23.86% ± 15.14%), dabigatran (28.30% ± 14.18%), edoxaban (38.76% ± 24.25%), low-molecular-weight heparin (53.28% ± 8.40%), apixaban (71.81% ± 10.92%), placebo (76.26% ± 14.61%), aspirin (86.32% ± 25.74%), and warfarin (87.95% ± 11.27%). No statistically significant heterogeneity was observed between trials. Conclusions and relevance According to our results, all anticoagulant drugs showed some effectiveness for VTE prophylaxis. Our ranking indicated that fondaparinux and rivaroxaban were safer and more effective than other anticoagulant drugs for patients undergoing THA or TKA.